God moves in mysterious ways: Faith units and their influence on prison governance in Argentina and Sweden - Pedrosa, Albert (European journal of criminology, 2024)
Faith-based units are prison spaces centred on the performance of religious practices that can nowadays be found in prisons in several countries. These faith-based practices have usually been explored in relation to the effects they have on inmates, but there are few studies that have explored how their presence affects prison life and how they can influence prison governance. This article will compare two different faith-based prison experiences located in two very different social and penitentiary contexts, Argentina and Sweden, in order to explore how the presence of these units affects prison management. To do so, we will analyse semi-structured interviews with 55 individuals conducted in prisons in both countries.